Post-traumatic stress disorder and associated factors among high school students who experienced war in Woldia town - Kassa, Mulat Awoke; Fenta, Sefineh; Anbesaw, Tamrat; Tesfa, Natnael Amare; Zemariam, Alemu Birara; Kassaw, Genanew Mulugeta; Abate, Biruk Beletew; Semagn, Elsabet Gezmu (Frontiers in Psychiatry, 2024)
The experience of war in recent time is very common around the world and the impact is profound in mental health of the victims, especially among young population. The most implicated mental health problem is Post-Traumatic Stress Disorder, which comes after exposure to trauma as a severe and long-term result of the traumatic event. Studies in developed countries revealed this finding, but there is insufficient information in developing countries, where much of war and conflict exist and young population live including Ethiopia. Therefore, this study aim s to assess the prevalence and associated factors of Post-Traumatic Stress Disorder among high s chool students who experienced war. Objective: We assessed the prevalence and factors associated with Post-Traumatic Stress Disorder among high school students who experienced war. Methods: Multi-Centered school base cross-sectional study was conducted from May 23 to June 08, 2022. Data were collected from high school students in Woldia town. Bivariable and multivariable logistic regression was used to identify the independent factors associated with post-traumatic stress disorder. Results: A total of 338 of the 410 students participated in this study (94.5% response rate). The prevalence of Post-Traumatic Stress Disorder was 39.2%. In the multivariable analysis, poor social support(AOR =3.40, 95 % CI: 1.45, 7.95), depression(AOR=3.24, 95% CI:1.69,6.21), high level of perceived stress(AOR=2.98, 95 % CI: 1.61, 5.50),being in war fighting situation(AOR=2.85, 95 % CI: 1.40, 5.78), and witnessing the murder of family members or friends(AOR= 3.05, 95 % CI : 1.47, 6.32) were factors significantly associated with Post-Traumatic Stress Disorder at p-value of < 0.05. Conclusions and recommendations: Around two in five of high school students had Post-Traumatic Stress Disorder in this study. Independent factors of PTSD were depression, high stress levels, poor social support, witnessing the murder of family members/friends, and being in war fighting situation. We recommend that the Ministry of Education and the Ministry of Health collaborate to integrate mental health services into schools. This focus on early detection of students at risk of PTSD, such as those with depression, high perceived stress levels, exposure to murder, or war, and provide necessary social support to prevent PTSD.